Element-Selective Targeting of Nutrient Metabolites in Environmental Samples by Inductively Coupled Plasma Mass Spectrometry and Electrospray Ionization Mass Spectrometry - Li, Jingxuan; Boiteau, Rene M.; Babcock-Adams, Lydia; Acker, Marianne; Song, Zhongchang; McIlvin, Matthew R.; Repeta, Daniel J. (Frontiers in Marine Science, 2021)
Metabolites that incorporate elements other than carbon, nitrogen, hydrogen and oxygen can be selectively detected by inductively coupled mass spectrometry (ICPMS). When used in parallel with chromatographic separations and conventional electrospray ionization mass spectrometry (ESIMS), ICPMS allows the analyst to quickly find, characterize and identify target metabolites that carry nutrient elements (P, S, trace metals; “nutrient metabolites”), which are of particular interest to investigations of microbial biogeochemical cycles. This approach has been applied to the study of siderophores and other trace metal organic ligands in the ocean. The original method used mass search algorithms that relied on the ratio of stable isotopologues of iron, copper and nickel to assign mass spectra collected by ESIMS to metabolites carrying these elements detected by ICPMS. However, while isotopologue-based mass assignment algorithms were highly successful in characterizing metabolites that incorporate some trace metals, they do not realize the whole potential of the ICPMS/ESIMS approach as they cannot be used to assign the molecular ions of metabolites with monoisotopic elements or elements for which the ratio of stable isotopes is not known. Here we report a revised ICPMS/ESIMS method that incorporates a number of changes to the configuration of instrument hardware that improves sensitivity of the method by a factor of 4-5, and allows for more accurate quantitation of metabolites. We also describe a new suite of mass search algorithms that can find and characterize metabolites that carry monoisotopic elements. We used the new method to identify siderophores in a laboratory culture of Vibrio cyclitrophicus and a seawater sample collected in the North Pacific Ocean, and to assign molecular ions to monoisotopic cobalt and iodine nutrient metabolites in extracts of a laboratory culture of the marine cyanobacterium Prochorococcus MIT9215.